2020
DOI: 10.3390/agronomy10020222
|View full text |Cite
|
Sign up to set email alerts
|

A Generic Model Accounting for the Interactions among Pathogens, Host Plants, Biocontrol Agents, and the Environment, with Parametrization for Botrytis cinerea on Grapevines

Abstract: Although the use of biocontrol agents (BCAs) to manage plant pathogens has emerged as a sustainable means for disease control, global reliance on their use remains relatively insignificant and the factors influencing their efficacy remain unclear. In this work, we further developed an existing generic model for biocontrol of foliar diseases, and we parametrized the model for the Botrytis cinerea–grapevine pathosystem. The model was operated under three climate types to study the combined effects on BCA efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 69 publications
1
23
0
Order By: Relevance
“…eres , they can be assumed as representative, because intraspecies variability was never reported. There are several examples regarding the projection of quantitative data on fungal ecology in predictive models, like Botrytis cinerea for grapes [ 64 ] or Fusicladium eriobotryae in loquat [ 65 ], and that is the challenge also for D . eres in hazelnut.…”
Section: Discussionmentioning
confidence: 99%
“…eres , they can be assumed as representative, because intraspecies variability was never reported. There are several examples regarding the projection of quantitative data on fungal ecology in predictive models, like Botrytis cinerea for grapes [ 64 ] or Fusicladium eriobotryae in loquat [ 65 ], and that is the challenge also for D . eres in hazelnut.…”
Section: Discussionmentioning
confidence: 99%
“…The agents either antagonize or parasitize the pathogen on the host surface, or they occupy potential infection sites [47]. BCAs, therefore, influence I, N, and i [48].…”
Section: Fungicide Sprays and Other Tactical Actions Against The Pathmentioning
confidence: 99%
“…Temperature, humidity, and other environmental conditions have been evaluated as key factors determining BCA efficacy (Mitchell et al, 1987;Jackson et al, 1991;Elad et al, 1993;Hannusch and Boland, 1996;Dik et al, 1999;Kredics et al, 2003;Fedele et al, 2020c), but the complex relationships between BCAs and multiple environmental factors remain poorly understood (Deacon and Berry, 1993;Whipps, 1997). Fedele et al (2020a) recently used a general model to study how control of BBR by a theoretical BCA is affected by the control mechanism, timing of BCA application, and environmental conditions. The authors found that temperature and moisture conditions affecting the growth and survival of the theoretical BCA were more important than its mechanism of control or the timing of its application.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the extensive research on BCAs ( O’Neill et al, 1996 ; Schoene, 2002 ; Jacometti et al, 2010 ; Calvo-Garrido et al, 2014 ; Pertot et al, 2017 ; Calvo-Garrido et al, 2018 ; Escribano-Viana et al, 2018 ; Rotolo et al, 2018 ; Calvo-Garrido et al, 2019 ; Fedele et al, 2020a ), only a few commercial products containing BCAs are available in Europe ( Nicot et al, 2016 ), where farmers still mainly rely on chemical fungicides for BBR control. The limited use of BCAs for BBR control may be related to their inconsistent efficacy across seasons or across local agronomic conditions ( Tracy, 2014 ; Calvo-Garrido et al, 2019 ), i.e., multiple factors and complex processes generally determine BCA efficacy ( Rosenheim et al, 1995 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation